Efektywność gospodarki finansowej samodzielnych publicznych zakładów opieki zdrowotnej - Susmarski, Sebastian; Gwizdała, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Some dissatisfaction with the methods of finance and delivery of health care has emerged in all of the Member States. Main common problems, albeit to different degrees, are deficiency of systems to cope with changing disease patterns, to provide equitable access to services, maintain control over costs, to utilise health care resources efficiently and to provide high quality medical care. Common concerns result in similar and different strategies for solution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 469-477